MATURATIONAL DEVELOPMENT, COLOUR PERCEPTION AND TRITAN RESPONSES - Lillo Jover, Julio; Collado, José A.; Sánchez, Mª Pilar; Pitini, Isaac (Anales de Psicología / Annals of Psychology)
Chromatic competence was evaluated in 788 schoolboys, with ages ranging from 5 to 7 years old, by means of a set of three tests: Ishihara, CUT (City University Test) and TIDA (Test de Identificación de Daltonismos). Prevalence of chromatic pathologies was similar to that in the European population. A trend to show tritan responses at non-pathological level was also found among the youngest children. Possible explanations for this fact are discussed.